The Effect of Regular Exercise Training on Serum Level of Malondialdehyde - Mahmoud, Tayfoor Jalil (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: Poly unsaturated fatty acids(PUFAs ) that contain two or more double bonds are particularly susceptible to oxidation by free radicals and other highly reactive species. Malondialdehyde( MDA) is one of many low molecular weight endproducts of lipid hydroperoxide decomposition and is the most often measured as an index of lipid peroxidation. The aim of the present study was to measure the serum level of MDA in healthy non athletics and athletics. Methods : This study was carried out during the period from April 2007 to September 2007 on 53 healthy non athletics (27 males and 26 females), and 31 healthy athletics (16 males and 15 females). Serum MDA level was measured colorimetrically using thiobarbituric acid method . Results: The mean value of serum MDA was significantly higher in healthy athletics than that of healthy non athletics (p<0.05). The mean value of serum MDA in females was non significantly higher than that of males (p>0.05) in both groups . The mean value of serum MDA was significantly higher in healthy non athletic smokers than that of non smokers (p<0.001) . Conclusion: Based on the findings of the present study , it can be concluded that regular exercise training causes excess lipid peroxidation and generation of significant amounts of MDA, one of the most important harmful free radicals .Therefore athletics should take a diet rich in antioxidants or appropriate amount of antioxidant vitamins ( A, C,and E) .